PROSPECTS FOR THE APPLICATION OF INTERNATIONAL FINANCIAL REPORTING STANDARDS IN THE PRACTICE OF UZBEKISTAN - Zufarova Zilola Rakhim kizi, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article describes the essence of international financial reporting standards and the goals of their application. As a result of the research, recommendations were developed for the introduction of international financial reporting standards into the practice of our country.